Entomological and parasitological study on phlebotomine sandflies in central and northern Albania - Velo E.; Paparisto A.; Bongiorno G.; Di Muccio T.; Khoury C.; Bino S.; Gramiccia M.; Gradoni L.; Maroli M. (Parasite, 2005)
An entomological survey was carried out in two districts of central (Kruje) and northern (Lezhe) Albania. Six collecting sites, showing a variety of diurnal resting sites, were monitored for adult sandflies from June through October 2002. Flies were collected with CDC miniature light traps, sticky traps and mechanical or hand aspirators in peridomestic sites, in bedrooms and inside cow barns, chicken coops and pigpens. All collecting sites monitored were found positive for sandflies. A total of 849 specimens were caught (29.2 % males) belonging to five Phlebotomus species. Phlebotomus neglectus (75.6 %) was the most abundant species followed by P. perfiliewi (14.4 %), P. papatasi (4.6 %), P. tobbi (3.6 %) and P. similis (1.8 %). The first adult of P. neglectus appeared on June 11 and the last one was collected on October 16. The highest density for this species was observed at the end of July. A total of 111 blood-fed females were caught from the two areas studied. P. neglectus was the only species found blood fed in Lezhe and the same species was prevalent (56.1 %) in Kruje followed by P. perfiliewi (30.3 %), P. tobbi (10.6 %); P. papatasi was represented by only two specimens. Blood meal origin was determined in 45/66 (68.2 %) of the females tested from Kruje district. P. neglectus was found fed on four hosts, showing the following feeding patterns: cow (71.4 %), dog (17.1 %), chicken (5.7 %) and human (5.7 %) ; P. perfiliewi was found fed on cow (80.0 %) and chicken (20.0 %), P. tobbi on cow (50.0 %), chicken (25.0 %) and dog (25.0 %). One specimen of P. papatasi was found fed on cow. When such prevalences were analysed by the available biomass for each host present at the collecting site, P. neglectus resulted to be an opportunistic feeder rather than exhibiting preferences for any specific animal. PCR analysis of 39 P. neglectus from the Lezhe district gave negative results for the presence of Leishmania DNA.